2016
DOI: 10.3747/co.23.3123
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in the Management of Metastatic Gastric Cancer in Ontario

Abstract: Background Geographic variation in cancer care is common when clear clinical management guidelines do not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…This may be due, in part, to the maturity of the HIV care infrastructure in the province. Previous studies of inter-provincial variation in HIV testing rates have suggested that coordinating all HIV care in the province through a single center may produce better outcomes, by allowing for closer monitoring of PLHIV and better control over standards of care [35], and regional variation tends to be larger when well-defined standards of care and guidelines are absent [2]. Furthermore, the small variation in ART costs among those receiving ART, is likely a result of the evolution of ART treatment, with simpler and safer regimens [36], easing some of the burden on rural health regions by lessening the requirement for highly-specialized clinics and physicians to treat PLHIV effectively [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due, in part, to the maturity of the HIV care infrastructure in the province. Previous studies of inter-provincial variation in HIV testing rates have suggested that coordinating all HIV care in the province through a single center may produce better outcomes, by allowing for closer monitoring of PLHIV and better control over standards of care [35], and regional variation tends to be larger when well-defined standards of care and guidelines are absent [2]. Furthermore, the small variation in ART costs among those receiving ART, is likely a result of the evolution of ART treatment, with simpler and safer regimens [36], easing some of the burden on rural health regions by lessening the requirement for highly-specialized clinics and physicians to treat PLHIV effectively [30].…”
Section: Discussionmentioning
confidence: 99%
“…Regional variation in health care costs after adjustment for demographic and clinical factors can be indicative of inequities or a lack of well-defined clinical practice [1, 2]. This topic has been the subject of considerable research in the United States and elsewhere [1, 35], primarily to facilitate performance-based reimbursement or identify potentially inefficient health care providers [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When adequately validated, these databases can provide important data such length of stay and related costs, 31 important outcomes such as adverse events 32 33 as well as variations in healthcare resource utilisation. 34 Indeed, administrative databases are readily available for the whole of Italy, whereas cancer registry data are not. Thus, our proposed validation method using a well-defined case definition can be a good alternative in settings in which cancer registries are not available in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…This will be a pragmatic, multicentre, waitlist group-controlled, investigator and analyst-blinded, 3-arm parallel-group superiority RCT with 1:1:1 allocation (figure 2). Randomisation will be stratified by recruitment site to account for differences in care across centres34 with block sizes of 6 and 9 within each stratum. Reporting of this protocol is in accordance with the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines35 (see online supplementary additional file for SPIRIT checklist).…”
Section: Methodsmentioning
confidence: 99%